Child Migration and Human Rights in a Global Age - Martuscelli, Patrícia Nabuco (Meridiano 47 - Journal of Global Studies, 2017)
BHABHA, Jacqueline. Child Migration and Human Rights in a Global Age.Princeton: Princeton University Press, 2014. 336p. ISBN 978-0-691-14360-6.